The Impact of Cooperative Learning on Developing Speaking Ability and Motivation Toward Learning English - Ehsan Namaziandost; Vida Shatalebi; Mehdi Nasri (National Research University Higher School of Economics, 2019)
This study aimed to investigate the effectiveness of cooperative learning in English language classrooms to enhance Iranian students' speaking skills and motivations. A pre-test-post-test control group design was employed to compare the impact of the cooperative learning approach with that of traditional whole-class instruction on speaking skills and six aspects of learning motivation: intrinsic motivation, integrated regulation, identified regulation, introjected regulation, external regulation, and amotivation. The data of the current study were gathered at multiple points of time before and after the end of the experiment to determine the effectiveness of cooperative learning on the sample's speaking skills and motivations. In practical terms, the sample's speaking skills were first examined through an English oral test prior to and after some cooperative learning instructional activities were provided. Next, a seven-point Likert scale-questionnaire was administered to the sample before and at the end of the course to check students' motivation towards the use of cooperative learning in English classes. The data were analyzed using basic and inferential statistical methods including mean scores, standard deviations, independent and paired sample t-tests, one-way ANCOVA, and effect size. The findings showed remarkable development in the students' speaking skills after the introduction of cooperative learning techniques. Moreover, the findings suggested significant differences in favor of cooperative learning for improving intrinsic motivation, but no differences were found on other aspects of motivation. In light of the findings, the researchers recommend that teachers could benefit from applying CL in English classes, which may in turn develop students' speaking skills and motivation.